A tutela constitucional da investigação criminal - Alves, Joaquim Dias (2016)
This work aims at studying the criminal prosecution, the application of constitutional principles of Democratic Rule-of-Law State and their effects on the constitutional legal system. In order to accomplish this goal, we started off by researching the origin and organization of the State, from ancient Greece to the beginning of the XXI century. Then, we looked for, in the origin of constitutional law, the fundamental and criminal procedural principles which establish the criminal prosecution of the State and the legal relationship among the branches of Public Law. In the Democratic Rule-of-Law State, the procedural instrumentality of the application of substantive law follows several principles. Among them, human dignity, due legal process, and full legal defense as foundation of law and justice. We found out that, to perform the prosecution, the Democratic Rule-of-Law State has bodies that carry out these important functions. They are: the judicial police, which investigates criminal offenses and their authors; the Public Prosecutor Office, as a permanent safeguard of legality, proposing the criminal action; the lawyer, to defend the rights and guarantees of the accused and finally, the Judiciary, performing judicial functions, applying the law to each specific case, and exercising the State’s right to punish. In this study, we also tried to examine the criminal investigation from the point of view of the procedural legal character, and its legality, in the procedural legal relationship. We carried out a historical study of the evolution of investigation up to the emergence of police inquiry and the judicial police, the latter as the institution in charge of that function, which is constitutional, today. Finally, we sought to establish that the criminal investigation in the processing of police inquiry is essential not only for the prosecution, but as prerequisite for criminal prosecution